2015
DOI: 10.1093/femsle/fnv031
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new ViI-like Erwinia amylovora bacteriophage phiEa2809

Abstract: Erwinia amylovora is a Gram-negative plant pathogenic bacteria causing fire blight disease in many Rosaceae species. A novel E. amylovora bacteriophage, phiEa2809, was isolated from symptomless apple leaf sample collected in Belarus. This phage was also able to infect Pantoea agglomerans strains. The genome of phiEa2809 is a double-stranded linear DNA 162,160 bp in length, including 145 ORFs and one tRNA gene. The phiEa2809 genomic sequence is similar to the genomes of the Serratia plymutica phage MAM1, Shigel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Both of these Pantoea phages, namely bacteriophages LIMElight and LIMEzero, are classified within the Autographivirinae subfamily of the Podoviridae . However, a number of broad-host range Erwinia or Serratia phages have been reported to be able to infect bacteria from the genus Pantoea [ 4 , 5 , 6 , 7 , 8 , 9 , 16 ]. To our knowledge, all of these bacteriophages, with the exception of siphoviruses PhiEaH1 [ 12 ], PhiEaH2 [ 13 ], KEY [ 14 ], and phiOT8 [ 16 ], have been assigned to the families Myoviridae or Podoviridae .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these Pantoea phages, namely bacteriophages LIMElight and LIMEzero, are classified within the Autographivirinae subfamily of the Podoviridae . However, a number of broad-host range Erwinia or Serratia phages have been reported to be able to infect bacteria from the genus Pantoea [ 4 , 5 , 6 , 7 , 8 , 9 , 16 ]. To our knowledge, all of these bacteriophages, with the exception of siphoviruses PhiEaH1 [ 12 ], PhiEaH2 [ 13 ], KEY [ 14 ], and phiOT8 [ 16 ], have been assigned to the families Myoviridae or Podoviridae .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been shown that a number of completely sequenced Erwinia bacteriophages are active on bacteria from the genus Pantoea [ 4 , 5 , 6 , 7 , 8 , 9 ]. It is not surprising, because Pantoea is closely related to Tatumella and Erwinia , the three forming a monophyletic group nested within the other enterobacterial genera, such as Escherichia , Salmonella , Citrobacter , Enterobacter , Klebsiella, and Cronobacter [ 1 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the apple orchard in Yongin, South Korea where phiEaP-8 was isolated has never been infected with either E. amylovora or E. pyrifoliae . In a previous paper ( Lagonenko et al, 2015 ), phiEa2809 was isolated from the leaves of an apple tree without fire blight symptoms in an apple orchard where fire blight was never detected. The genus Erwinia is classified to the Enterobacteriaceae family, which includes both pathogenic and non-pathogenic bacteria in genera such as Erwinia , Enterobacter , Pantoea , Pectobacterium , and Brenneria ( Kado, 2006 ).…”
mentioning
confidence: 99%
“…Both S2 and Bue1 encode putative exopolysaccharide (EPS) depolymerases, which degrade the amylovoran component of the host’s capsule ( 12 ). Similar genes are present in E. amylovora phages vB_EamP-L1 (GenBank accession number NC_019510 ; T7virus) ( 4 ), Ea9-2 (GenBank accession number NC_023579 ; Ea92virus) ( 13 ), and phiEa2809 ( 14 ). This widespread prevalence of EPS depolymerases among E. amylovora podoviruses and myoviruses indicates an importance in host infection and specificity.…”
Section: Announcementmentioning
confidence: 88%